Method development and validation of aspirin and clopidogrel pharmaceutical dosage forms by developing new RP HPLC method - Dharani Sai Sreekanth, Nellore; Adilakshmi, Nenavath (Creative Pharma Assent, 2020)
A simple and selective LC method is described for the determination of Aspirin and Clopidogrel in tablet dosage forms. Chromatographic separation was achieved on a c18 column along with mobile phase consisting of a combination of fifty five volumes of Mixed Phosphate Buffer and forty five volumes of Acetonitrile with detection of 235 nm. Linearity was observed in the range 20-60 μg/ml for Aspirin (r2=0.998) and 10-30 μg /ml for Clopidogrel (r2 =0.998) for the amount of drugs estimated by the projected ways was in smart agreement with the label claim. The proposed methods were validated. The accuracy of the methods was assessed by recovery studies at three different levels. Recovery experiments indicated the absence of interference from commonly encountered pharmaceutical additives. The method was found to be precise as indicated by the repeatability analysis, showing %RSD trials. All statistical data proves validity of the ways and may be used for routine analysis of pharmaceutical dosage form.